"Gammfolket" : Om livserfarenheter och vardagens ålderism - Snellman, Fredrik (Umeå universitet, Institutionen för socialt arbete, 2009)
The overall aim of this thesis is to describe and analyse the age-related life experiences of elderly retired people and in relation to this to problematise ageism as an analytical concept in order to present a more dynamic understanding of the phenomenon of ageism in everyday life. Related to the overall objective three overarching research questions are addressed. How do elderly individuals relate to “age” in life and how do they express this in contexts in which standpoints are made in relation to age-codes? What can be generally said to represent the foundation of elderly people’s experiences of ageism? What all-embracing picture of ageism and age-coding is made visible when the phenomenon is examined using different kinds of methods for collecting and analysing empirical material? Research within the field of ageism is presented in terms of how it has been examined: as an ideology, as an “ideology” that is possible to deconstruct and as manifestations in everyday life. The hegemonic way of defining ageism is to associate it with prejudice, stereotyping and discriminationbased on age. This is viewed to be insufficient in order to understand ageism in everyday life. The positioning of the thesis in relation to the research field is therefore seen as problematising ageism as an analytical concept. The thesis consists of three different studies that are based on three different empirical materials. Life-stories, a questionnaire and focus group interviews are used to collect empirical material on the subject of elderly people’s age-related life experiences. The empirical materials and the studies connected to them are distinct ways of investigating ageism. Tentatively, methodtriangulation is applied in order to analyse the topic of ageism in everyday life from differenttheoretical perspectives. The most important conclusion is that ageism can be understood more dynamically as a practise that is exceptionally close to us individuals in everyday life. It is suggested that ageism is not only associated to age. Informants use alternative age-markers or time-markers in relation to which theyascribe meaning. When individuals tell their life-story the experiences are for example not tied to age. Age is hardly ever mentioned. In its place meaning is constructed around and ascribed to timemarkers such as for example “young”, “old”, “year”, “month”, “elderly” and so on. The use of and ascription of meaning to time-markers is also applicable in the other studies in the thesis. These alternative time-markers are suggested as something that also indicate ageism. Experiences and meaning are not solely focused on age. However, the meaning constructed in relation to the alternative markers is not unanimous, even if it sometimes appears to be. The experienced meaning takes many different forms and can by no means be fixated once and for all. An important conclusion is also that we cannot disregard gender in the understanding of ageism. It seems imperative to practice intersectional reasoning in order to understand the dynamics of ageism. Gendered ageism or gendered time-coding is essential in comprehending what people experience in everyday life.